ARTISTIC PSYCHOLOGISTS IN ENGLISH AND UZBEK LITERATURE - Yusupova, Zilola Sunnatillo qizi; Jalilova , Lola (Educational Research in Universal Sciences, 2023)
This article discusses one of the most important topics of modern literature - the concept of artistic psychology and its history. As an introduction to the concept, theoretical views of literary scholars and definitions of the term by English and Uzbek scholars are given. In addition, some theories about the three principles of artistic psychology are mentioned in the discussion of the topic.